WATERS CARRYING CAPACITY FOR DEVELOPMENT OF SEAWEED CULTURE OF Eucheuma cottonii IN LUWU AND PALOPO DISTRICTS, BONE BAY, SOUTH SULAWESI - . Waluyo; . Yonvitner; Etty Riani; Taslim Arifin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
In seaweed Eucheuma cottonii cultures, a water carrying capacity is an important factor to optimize the seaweed culture. Carrying capacity can be determined by an ecological footprint production (EFp) analysis. This research was conducted in May 2015 (1st transitional season) and September 2015 (2nd transitional season) in Luwu and Palopo distircts, South Sulawesi. Map and land use were analyzed using GIS (Geographic Information Systems). The result showed that the ecological foot-print production (EFP) in Luwu waters was 67.88 ton/capita/year or equivalent to 235,823.93 tons/ year. However, based on the analysis of the water availability for seaweed was 59,781.79 hectares, it can produce seaweed (biocapacity) for 1,437,779.60 tons/year and the number of farmers that allows for use the waters is 21,432 capita. The ecological footprint  production (EFp) in Palopo waters is 3.08 ton/capita/year, or equivalent to 4,589.99 tons/year. Water availability analysis is 1,771. 41 hectares are able to produce seaweed (biocapacity) for  18,287.46 ton/year and the number of far-mers that allows for use the waters is 635 farmers capita. The results comparison between biocapa-ci-ty and ecological footprint, ecological status for  Luwu and Palopo waters are still in sustainable use.